Effect of bamboo charcoal additions on shear strength and fracture behaviour of SN-BI solder joint - Chai, Jing Yee (2024)
Sn-Bi solders are considered by PV manufacturers as acceptable Pb-free alternative due to its low operating temperature and cost, despite being prone to brittleness caused by coarse Bi phases. Bamboo charcoal (BC) is a sustainable and environment-friendly resource with large surface area and its addition to Sn-Bi solder creates a green solder that complies with environmental regulations. This study contributed to the development of a high-performance Sn-58Bi alloy, demonstrated BC’s role in enhancing solder joint reliability, and offered a sustainable alternative to Pb-based solders. The purpose of this study was to improve the shear strength and reduce the brittleness of the Sn-Bi solder alloy by adding a sustainable reinforcement (BC) to produce a low-cost, lowtemperature, safe, environmentally friendly, and sustainable reinforced solder. Sn-58Bi solder paste was reinforced with 0.25, 0.50, 0.75 and 1.00 wt.% of activated BC, respectively and and tested under accelerated aging at 120 °C for 7 and 14 days. Shear strength of the as-reflowed solder joints increased by about 21.67 % with 1.00 wt.% activated BC was added as reinforcement in the asreflowed condition, and the 14-day aged samples showed less degradation (31.14 %) compared to pure Sn-Bi solder (49.28 %). Fracture surfaces showed transitions from flat and smooth surface to elongated-dimple structures with the addition of activated BC. Prolonged accelerated aging increased cleavage presence, while increasing amounts of activated BC reduced facet numbers and void size, indicating successful suppression of Bi phase segregation. Furthermore, no Mode 3 failures (failure in the intermetallic compound (IMC) layer) occurred when the as-reflowed samples contained 0.50 wt.% or more of activated BC, and the 7- and 14-day heat-aged samples were free from Mode 3 failures when the activated BC composition was at 0.75 wt.% and above. From this study, the recommended composition for improved PV module performance was determined to be Sn-58Bi with 1.00 wt.% activated BC.